2016
DOI: 10.1007/s12144-016-9492-5
|View full text |Cite|
|
Sign up to set email alerts
|

Why Is Theory of Mind Important for Referential Communication?

Abstract: This research studies the relation between children’s Theory of Mind (ToM) and the communicative behaviour and strategies used in a referential communication task. A total of 46 children (aged 6 to 10) were administered 6 ToM tasks, and they also participated in pairs in a cooperative task. Each pair built 4 construction models. Results showed that several ToM skills were related to the communicative behaviours of requesting clarification and giving information. In addition, the most used communicative strateg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
9
0
2
Order By: Relevance
“…Resches and Pérez Pereira (2007) point out that ‘the capacity to take into account mental states in others seems to be a key factor which regulates communicative interchanges’ (p. 22). They showed that children with higher level ToM abilities were more adept at regulating communication (see also Graham, San Juan, & Khu, 2017; Roby & Kidd, 2008; Sidera, Perpiñà, Serrano, & Rostan, 2018 for the relationship between Theory of Mind and referential communication) since they were able to understand and anticipate the behaviors of others. While their results were based on production, we might assume that intonation and facial gesture would be some of the cues children might exploit in order to assess and ultimately predict the behavior of another individual in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…Resches and Pérez Pereira (2007) point out that ‘the capacity to take into account mental states in others seems to be a key factor which regulates communicative interchanges’ (p. 22). They showed that children with higher level ToM abilities were more adept at regulating communication (see also Graham, San Juan, & Khu, 2017; Roby & Kidd, 2008; Sidera, Perpiñà, Serrano, & Rostan, 2018 for the relationship between Theory of Mind and referential communication) since they were able to understand and anticipate the behaviors of others. While their results were based on production, we might assume that intonation and facial gesture would be some of the cues children might exploit in order to assess and ultimately predict the behavior of another individual in conversation.…”
Section: Discussionmentioning
confidence: 99%
“…Extending from this point, cooperation via spoken language connects with the theory of mind, which is known to be significant in pragmatic language processing and shared social interactions as interlocutors acknowledge different mental states, such as one’s own and other’s beliefs, aspirations and intentions. This cognitive ability is crucial for the information processing and behavioral regulation required to overcome the ambiguity of meaning necessary for efficient referential communication during reciprocal cooperative social exchanges (Liu et al, 2016; Paunov et al, 2019; Saxe and Kanwisher, 2003; Sidera et al, 2018). Therefore, results of our meta-analysis suggest that frontal and temporoparietal regions are not only involved in processing information during collaboration in separated brains, but actually synchronization between different brains in these regions plays a crucial role.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in classical false-belief tasks, 3-to 4-year-olds are able to keep track of and reproduce specific information that a play-partner has not seen due to being absent at the time when the information was provided [16]. Previous studies indicate that there is a link between performance on various ToM tasks, including false-belief tasks, and the ability to use common ground information during referential comprehension and production in early and middle childhood (ages 3-10) [17][18][19]. However, 4-to 6-year-olds do not use information regarding the visual perspective of interlocutors during online production to the same extent as adults [4,20].…”
Section: Development Of Common Ground Use During Online Communicationmentioning
confidence: 99%